Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

The discrete Fourier transform is defined as: $$S(k)=\sum_{n=0}^{N-1}s(n)e^{-j\frac{2\pi}{N}kn}\quad k=0,...,N-1$$ I read that real signals $s(n)$ are: $$S(l)=S(N-l)^*$$ where $S(N-l)^*$ is the conjugated complex number of $S(N-l)$.

I am trying to prove that, but I can't get it right. I can't accept it without a proof.^^

share|cite|improve this question
Your formula for $S(n)$ is incorrect since $n$ is an argument on the left side and a index of summation on the right. Please correct your formula before attempting any proofs. – Dilip Sarwate May 8 '12 at 1:17
up vote 0 down vote accepted

Put $e^{2\pi j/N}=:\omega$ and note the rules $\omega^*=\omega^{-1}$, $\omega^N=1$. It follows that the formula for the discrete Fourier transform can be written as $$S(k):=\sum_{n=0}^{N-1} s(n)\omega^{-kn}=\sum_{n=0}^{N-1} s(n)(\omega^*)^{kn}\ .$$ Now take on both sides the conjugate. If the $s(n)$ are real you get $$S(k)^*=\sum_{n=0}^{N-1} s(n)\omega^{kn}=\sum_{n=0}^{N-1} s(n)\omega^{-(N-k)n}==S(N-k)\ .$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.